Determinant Quality Of Regional And Financial Statements (Study On Local Government Regency Of Lombok Timur) (International Journal of Scientific Research and Management (IJSRM), 2017)
This paper aims to test and evince from some previous researches : the influence of the SAP Application, the Regional Financial Information System and the Reconciliation of the Quality of Regional Financial Statements. This is an explanatory research with purposive sampling method of interpretation. Data analyzed method. Analyzed with SmartPLS 3.0, the results of this test showed that the Application of SAP and Regional Financial Information System has a positive and significant impact on the Quality of Regional Financial Reports. While different results show that Reconciliation is not significant affect the quality of financial statements. The results of these trials will then be re-examined in subsequent research with larger samples and Determinants of the quality of wider regional financial statements and their implications for decision making.